2017
DOI: 10.1016/j.envpol.2016.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Presence of plastic particles in waterbirds faeces collected in Spanish lakes

Abstract: Plastic intake by marine vertebrates has been widely reported, but information about its presence in continental waterfowl is scarce. Here we analyzed faeces of waterbirds species (European coot, Fulica atra, mallard, Anas platyrhynchos and shelduck, Tadorna tadorna) for plastic debris in five wetlands in Central Spain. We collected 89 faeces of shelduck distributed in four lakes, 43.8% of them presented plastic remnants. Sixty percent of 10 faeces of European coot and 45% of 40 faeces of mallard contained pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…In soils many hydrophobic and amphiphilic compounds also regulate species communication and ecosystem processes. For instance, hydrophobins are amphiphilic proteins ubiquitous in soils that are secreted by fungi (Rillig, 2005 (Steinmetz et al, 2016), ingestion by terrestrial and continental birds (Gil-Delgado et al, 2017;Holland et al, 2016;Zhao et al, 2016), reduction in growth of earthworms (Lwanga et al, 2016), lethal toxicity to fungi (Miyazaki et al, 2014(Miyazaki et al, , 2015Nomura et al, 2016), mammal lung inflammation (Hamoir et al, 2003;Oberdorster, 2000;Schmid & Stoeger, 2016) and broad cytotoxicity (Forte et al, 2016;Kato et al, 2003) of nanoplastics [Colour figure can be viewed at wileyonlinelibrary.com] stability, with direct potential consequences for soil erosion and biogeochemical cycles (Rillig, 2005). It was suggested that microplastics might present distinct sorption properties for soil inorganic elements (Hodson, Duffus-Hodson, Clark, Prendergast-Miller, & Thorpe, 2017), and laboratory results suggest that hydrophobins play a role in the protection against nanoplastic toxicity to filamentous fungi (Nomura et al, 2016).…”
Section: The Need For Accurate An D Precise Quantification Of Micromentioning
confidence: 99%
See 1 more Smart Citation
“…In soils many hydrophobic and amphiphilic compounds also regulate species communication and ecosystem processes. For instance, hydrophobins are amphiphilic proteins ubiquitous in soils that are secreted by fungi (Rillig, 2005 (Steinmetz et al, 2016), ingestion by terrestrial and continental birds (Gil-Delgado et al, 2017;Holland et al, 2016;Zhao et al, 2016), reduction in growth of earthworms (Lwanga et al, 2016), lethal toxicity to fungi (Miyazaki et al, 2014(Miyazaki et al, , 2015Nomura et al, 2016), mammal lung inflammation (Hamoir et al, 2003;Oberdorster, 2000;Schmid & Stoeger, 2016) and broad cytotoxicity (Forte et al, 2016;Kato et al, 2003) of nanoplastics [Colour figure can be viewed at wileyonlinelibrary.com] stability, with direct potential consequences for soil erosion and biogeochemical cycles (Rillig, 2005). It was suggested that microplastics might present distinct sorption properties for soil inorganic elements (Hodson, Duffus-Hodson, Clark, Prendergast-Miller, & Thorpe, 2017), and laboratory results suggest that hydrophobins play a role in the protection against nanoplastic toxicity to filamentous fungi (Nomura et al, 2016).…”
Section: The Need For Accurate An D Precise Quantification Of Micromentioning
confidence: 99%
“…Zhao et al found microplastic present in the digestive tract of 94% of dead terrestrial birds with diverse foraging behavior in China (Zhao, Zhu, & Li, 2016). Microplastics in the guts of freshwater continental birds have also been reported (Gil-Delgado et al, 2017;Holland, Mallory, & Shutler, 2016), and microplastic from agricultural activities seem to be an important source (Gil-Delgado et al, 2017). In some cases, microplastic was considerably smaller than the usual food of those birds, which suggests microplastic ingestion to be either accidental or via trophic transfer (Zhao et al, 2016).…”
Section: The Need For Accurate An D Precise Quantification Of Micromentioning
confidence: 99%
“…2) It has been proved that microplastics can impact freshwater fish (e.g. Lechner et al, 2014;Sanchez et al, 2014;Biginagwa et al, 2016;Pazos et al, 2017), birds (Faure et al, 2012;Holland et al, 2016;Gil-Delgado et al, 2017) and even zooplankton organisms (Rosenkranz et al, 2009), which is economic and ecologically relevant. 3) Small plastic fragments may possibly have leaching rates of exogenous chemicals (trace metals and organic pollutants) higher than those given by macroplastics, due to their proportionally greater surface (Nakashima et al, 2012)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition to direct consumption of plastics, there is also the potential for indirect, or secondary, consumption of plastic pollution via prey that have ingested plastic debris (Nelms et al 2018). More-over, there are questions about retention, whether plastics are retained in the gut and eventually excreted or eliminated via feces or guano (Gil-Delgado et al 2017;e.g., Provencher et al 2018;Reynolds and Ryan 2018), or whether plastics accumulate over time in the gut or even outside the gut, in the tissues of organisms (Table 1). This pathway for how plastics enter organisms, and their fate inside organisms, is important to consider, especially for understanding how plastics move through food webs, whether they magnify up the food chain, and how this may facilitate plastic contamination in humans via seafood consumption.…”
Section: Introductionmentioning
confidence: 99%